Evaluating the breeding potential of yearling bulls - L. Corah; G. Kiracofe; M. McKee; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1979)
Two years of research with nine herds indicated one of two yearling bulls with a herd usually will sire most of the calves. In six of the nine cases, the bull we pre-evaluated as most sexually active was the sire of the most of the calves. So a brief pre-breeding libido evaluation may help estimate breeding potential. In data from one herd the bull dominant as a yearling continued to be dominant as a two-year-old. Our data also indicated active breeding yearling bulls easily breed more than 20 to 25 cows during their first breeding season.
Keywords: Cattlemen& #x27; s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Breeding potential; Yearling bulls